A Systems Approach to Test the Usefulness of a Model to Challenge Organisational Change - Silva, J. (Systemic Approaches in Social Structures, 6th National & International HSSS Conference, 2010)
The impact of a proposition concerning the split of the structure of a precision engineering company into two clusters was holistically analysed and verified for consistency, as regards the structure design parameters. A conceptual model supported by both the schools of strategists and structuralists was used as an audit tool for ordered questioning, debate, learning and dialectical discussion. Moreover, the Soft Systems Methodology (SSM), provided orientation to theoretical validation of the model whose outcomes identified the potential, desirable and feasible change of both manufacturing systems and production planning and control (PPC). A situational, hermeneutics, interpretivist, learning oriented process of enquiry, rather different from best practice views, was shown adequate to the problem nature and to the case study confirming the interest of the two clusters. Thus, formal planning and control procedures exhibited a very weak stand requiring both development in line with the contingency factors and complementarity with the other work co-ordination mechanisms. This holistic, systemic, strategic and structured approach produced the reviewing and reformatting of the manufacturing strategy decision areas and recommended that PPC procedures should be further analysed in detail, in order to fit the two clusters. To sum up, the audit tool was found useful and it was also able to identify potential change in a credible way, to classify it as desirable/undesirable by following a learning process and, to discuss its feasibility in the context of a specific organisational culture. Thus, SSM provided an original contribution to Operations Research through the design of complex organisations under a systems view.